Decoding Greenwashing: The Interplay of Consumer Behavior, Consumer Knowledge, and Sustainable Purchasing Among Generation Z - Alrizma, Vanya Rayi; Junipriansa, Donni (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: This study examines the impact of greenwashing on sustainable purchasing decisions among Generation Z, emphasizing the roles of consumer behavior and consumer knowledge. Given the increasing prevalence of misleading environmental claims, understanding how consumers respond to such tactics is crucial for fostering responsible consumption.Purpose: The research aims to analyze how awareness of deceptive environmental claims influences purchasing choices and to determine the extent to which consumer knowledge can mitigate the negative effects of greenwashing. Design/methodology/approach: This study employs a quantitative approach, collecting data from 180 Generation Z consumers in the Bandung Metropolitan Area. Hypothesis testing was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the relationships between greenwashing, consumer knowledge, and sustainable purchasing behavior.Findings/Result: The results indicate that consumer knowledge positively influences sustainable purchasing behavior. Conversely, greenwashing negatively affects consumer trust and purchasing decisions, demonstrating the detrimental impact of deceptive sustainability claims.Conclusion: The study highlights the importance of increasing consumer awareness and education on sustainability claims to prevent misleading practices. Businesses should adopt transparent sustainability practices, while policymakers should enforce stricter regulations to combat greenwashing.Originality/value (State of the art): This research contributes to a deeper understanding of consumer responses to corporate sustainability claims, particularly within Generation Z. It provides valuable insights for businesses and policymakers on promoting responsible consumption and combating greenwashing. Additionally, the study suggests directions for future research, including exploring additional factors influencing sustainable purchasing decisions and broader demographic influences to enhance generalizability.Keywords: consumer behavior, consumer knowledge, greenwashing, sustainable purchasing decisions, generation z